Hadith #4241 - Sunan Abi Dawud - Abdul Quddus bin al-Hajjaj al-Khulani عبد القدوس بن الحجاج الخولاني; Abdullah bin Salm عبد الله بن سالم; ibn Umar; Umayr bin Han'i al-Ansi عمير بن هانئ العنسي (Sunan Abi Dawud)
The Prophet (ﷺ) said: four (majestic) trials (fitnahs) will take place among this community, and in their end there will be destruction.
Grade: Da'if

Hadith #5058 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Junadah bin Abi Umayya; Ubada bin As-Samit; Umayr bin Han'i al-Ansi عمير بن هانئ العنسي (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) went to his bed, he would say: Praise be to Allah Who has given me sufficiency, has guarded me, given me food and drink, been most gracious to me, and given to me most lavishly. Praise be to Allah in every circumstance. O Allah! Lord and King of everything, God of everything, I seek refuge in Thee from Hell.
Grade: Sahih

Hadith #3876 - Sunan Ibn Majah - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Junadah bin Abi Umayya; Ubada bin As-Samit; Umayr bin Han'i al-Ansi عمير بن هانئ العنسي (Sunan Ibn Majah)
“There is no rich man or poor man but he will wish on the Day of Resurrection that he had been given the bare minimum of provision.”
Grade: